Germany and the European East in the twentieth century - Mühle, Eduard (Berg, 2003)
This work looks at the complicated relationship between Germany and the European East during the short twentieth century. It looks at the social, cultural and political contexts during the Weimar Republic, the Third Reich and the Federal Republic. Please note that images or diagrams have been excluded from this text due to copyright restrictions.
Keywords: Geopolitics -- Europe, Eastern.; Germany -- Foreign relations -- Europe, Eastern.; Europe, Eastern -- Foreign relations -- Germany.; Géopolitique -- Europe de l'Est.; Allemagne -- Relations extérieures -- Europe de l'Est.; Europe de l'Est -- Relations extérieures -- Allemagne.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Geopolitics; Diplomatic relations; Eastern Europe; Germany; Buitenlandse betrekkingen.